PENGERTIAN, HUBUNGAN, DAN IMPLEMENTASI SOFT SKILLS, PEMBELAJARAN AFEKTIF, DAN PENDIDIKAN KARAKTER DALAM PROSES BELAJAR MENGAJAR - Suganda, Dadang (Paraguna, 2017)
This paper is  the  result of the  author  who  has  participated in  various  trainings organized  by   the  Director  General   of Higher  Education,  Ministry  of National Education.  Based on that,  it can  be stated that  both soft skills,  effective  learning, and  character  education,  the three  are not in the  realm  related  to technical  skills, professional  scientific fields,  or things  that  are  motoric in nature.  All three  are  in the  area  ofpersonality competence. All three  are more closely related  to EQ., SQ., Heart,  to live together  and  to be than  with IQ,  hand,  head,  to do,  or to know.  Thus the  meaning of sofs skills,  character  education  is  not much  diferent from affective abilities.  However,  of course  there  are  diferences,  such  as  the  sofs skill gives  a broader picture  ofpersonality,  while  character  education provides a more specific and specific personality picture than  affective competence.  This can be seen  clearly from  the  many   and  broad  scope  of the  attributes  of soft skills,  as  well  as  the specific and  specific character  education goals  that  emphasize the  basic values  of character, namely honesty, smart, tough, and  caring. Efforts to carry out character education  in  the  ISBI  Bandung  environment will  be  confronted  with   the  main problem,  namely  the  ability  to make changes in the  level  of thought  patterns and patterns   of  action.    The   mindset   of  entering    into   the    realm,    namely    the implementation  of activities  carried  out in  the ISBI Bandung environment must be able  to  incorporate  elements  of the  basic  values   of character  into  each  activity carried  out.  The pattern of action  can  be in  the form  of building  synergy between lecturers   and   students.   The   synergy  between  lecturers  and   students  is   an intellectual capital to realize success..